1994
DOI: 10.1002/rcm.1290081212
|View full text |Cite
|
Sign up to set email alerts
|

Isotope ratio mass spectrometry: Analysis of wines from different european countries

Abstract: Natural stable isotope ratios for carbon, hydrogen and oxygen depend on the origin of the studied chemical compound. Such a precept is the basis of the control of the authenticity of food and especially alcoholic beverages. 13C/12C analysis of ethanol as well as 180/160 determination of water contained in wines from different European countries underline the importance of the photosynthetic pathway as well as of the environmental and climatological conditions of the vine. Interesting results in agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…These results demonstrate a geographical dependence of these parameters, as already observed for wine. 7 A correlation between enrichment in heavy isotopes and latitude was observed. For instance, lower 18 O contents are observed for the oils coming from the northern regions (e.g.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…These results demonstrate a geographical dependence of these parameters, as already observed for wine. 7 A correlation between enrichment in heavy isotopes and latitude was observed. For instance, lower 18 O contents are observed for the oils coming from the northern regions (e.g.…”
mentioning
confidence: 90%
“…Evapotranspiration is known to create an enrichment in heavy isotopes of oxygen and hydrogen in plant water. This is particularly observable for the 18 O/ 16 O ratio of the water of fruits from various areas of production, 6,7 and differences in 18 O values higher than 5% were found on comparing warmer and colder countries. This geographical dependence has also been reported by Koziet and Bricout 28 for the 18 O values of fruit juice sugar.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…3 Recently, measurements of the 18 O/ 16 O stable isotope ratio (expressed as δ 18 O) of water in wine have been used for wine authentication, and extensive databases of wine isotope ratios are now being developed. [4][5][6][7] These technologies have also been extended to fruit juice extracts, 8 concentrated spirits, 9 and other food authentication applications.…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotope ratio methods exploit these differences of origin, which leave a recognisable trace in the end product. In the case of tartaric acid, we found that 13 Therefore, stable isotope ratio measurements of carbon cannot be used to differentiate natural tartaric acid from synthetic ones, but allow a preliminary, inexpensive screening of synthetic samples with d…”
mentioning
confidence: 98%